Pemanfaatan Limbahdaun Nanas Sebagai Bahan Alternatiffiller Dalampembuatan Komposit : Dengan Variasi Posisi Serat Dan Jumlah Lapisan Serat - Reza Andreano D; Idral Amri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
At the moment composite is one of the alternative materials being developed and widely used in the industrial world. Composites that use natural fibers are chosen because they are also environmentally friendly besides cheap. One of the natural fibers around us and has good potential is pineapple leaf fibers. This study aims to determine the effect of the number of fiber layers and position of pineapple leaf fibers on the mechanical properties of composites where the resin used in this study is polyesther resin. In this study an analysis of the composite strength, elasticity and elasticity was carried out. This study uses pineapple leaf fibers with variations of 1 layer of fiber, 2 layers of fiber, 3 layers of fiber and variations in the position of the fibers, namely below, in the middle, above. The results showed that the highest mechanical properties were obtained by composites with 3 layers of fiber with tensile strength values of 65.09 MPa, flexural strength of 327.1 MPa and elastic modulus of 5917.3 MPa. The resulting composite has met fiberglass reinforced plastic specification standards for water treatment units based on SNI 7504:2011. Keywords: composite, fiber, pineapple leaves, polyesther